2022
DOI: 10.3390/machines10020080
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rotating Speeds on the Cavitation Characteristics in Hydraulic Torque Converter

Abstract: Hydraulic torque converter is a kind of high speed rotating machine using viscosity hydraulic oil as working medium, and its internal flow field is very complex. Thereby cavitation can occur easily in the working process, resulting in severe degradation of torque converter performance, noise, vibration and even failure. In order to reveal the effect of rotating speeds on the cavitation characteristics, a full flow passage geometry and a computational fluid dynamics (CFD) model with cavitation were developed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Previous research reported that cavitating bubbles mainly occurred in the stator and that the stall operating condition was the worst-case scenario [28]. Thus, this study focused on the transient cavitation behaviour at stall, when both the stator and the turbine are stationary.…”
Section: Cfd Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research reported that cavitating bubbles mainly occurred in the stator and that the stall operating condition was the worst-case scenario [28]. Thus, this study focused on the transient cavitation behaviour at stall, when both the stator and the turbine are stationary.…”
Section: Cfd Modelsmentioning
confidence: 99%
“…The corresponding deviations in the steady-state cavitation CFD model were 9.2% and 10.6%, and the transient cavitation model further reduced the prediction error to within 7.6% for both performance indices, indicating that the transient cavitation CFD model can predict the overall hydrodynamic performance with acceptable accuracy. Furthermore, the comparison between the noncavitation CFD model and the cavitation CFD model confirmed that the torque converter suffered from heavy cavitation, and the differences in the deviations between the two models indicated the cavitation degree [ [28]].…”
Section: Cfd Model Validationmentioning
confidence: 99%
“…Ran Zilin et al developed a cavitation suppression technique by slotting one side of the stator suction side, which was proven to be able to significantly shorten the cavitation duration (Ran et al, 2022). Guo Meng et al developed a full flow passage geometry and a computational fluid dynamics (CFD) model with cavitation to analyze the flow behavior in the torque converter (Guo et al, 2022a). Xiong Pan et al optimized the Joukowsky airfoil used in the design of stator blades, which greatly reduced the probability of cavitation and improved the performance and service life of the torque converter (Pan et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Chai et al (Chai et al, 2022) revealed the three-dimensional morphological characteristics of cavitation flow under extreme working conditions through high-precision numerical simulation and analysis of the cavitation flow field of a flat torque converter. Guo et al (Guo et al, 2021;Guo et al, 2022b) proposed full-flow CFD models with and without cavitation for torque converters, and studied the effects of different pump impeller speeds, pump turbine speed differences and cavitation parameters on the internal flow field of the torque converter. Xiong et al (Xiong et al, 2021) modified the torque converter stator blades through Joukowsky airfoil transformation, which greatly reduced the probability of cavitation.…”
Section: Introductionmentioning
confidence: 99%
“…Основной рабочий режим гидромеханической трансмиссии погрузчика находится в диапазоне малых передаточных отношений ГДТ, когда трансмиссия погрузчика испытывает высокие нагрузки (например, при заборе грунта ковшом). Согласно исследованиям [13], на таких режимах есть высокий риск образования кавитации.…”
unclassified